Recruitment of Indigenous Study Participants in Canada: Obligations or Constraints? An Ethical Reflection - Farrugia, Patricia (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Recruitment of study participants from marginalized populations present unique challenges for researchers and associated institutions. Researchers must be aware of the specific adaptations required in the research process in conducting research within and Indigenous populations. Cultural consciousness is key with any research conducted within these populations to understand the past issues that can influence present and future willingness to participate in research. This article aims to provide context and examples where increasing cultural awareness of specific ethical principles during the recruitment phase can affect the study process as well as the researcher themselves. Integrating Indigenous cultural concepts within the recruitment and study design process can help to lay the groundwork for a positive research process as a whole and facilitate an appropriate study environment for all involved.